Consumo recomendado de frutas, legumes e verduras na região Centro-Oeste do Brasil : prevalência e fatores associados segundo o sistema de vigilância de fatores de risco e proteção para doenças crônicas por inquérito telefônico (Vigitel), 2012 - Damiani, Thaís Fernanda (2015)
The consumption of fruits and vegetables (FV) has been associated with decreased risk of mortality and the prevention of chronic diseases such as cardiovascular disease. Eating a variety of these foods is important because they are sources of micronutrients, fiber and others nutritionally factors. Furthermore, it can replace food containing high concentrations of saturated fats, sugar and salt. Promoting the consumption of FV is recommended by World Health Organization as a priority in nutrition, food and agriculture policies. Objective: Describe the FV intake prevalence and analyze its associated factors among adults living in Midwest of Brazil. Methods: A cross-sectional study, based on data, collected in 2012, from the system Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (VIGITEL – telephone-based surveillance of risk and protective factors for chronic diseases) among individuals aged ≥ 18 years, living in Brazil’s Midwest region. To analyze associations between FV adequate consumption and the independent variables, Poisson Regression was performed, considering 95% of confidence intervals. Results: Adequate FV intake prevalence was low in the studied population (26,3%) being higher among women (RPaj= 1,44; IC 95% = 1,29 – 1,62). For both gender, it was observed a direct association between years of study, regular physical activity and the adequate FV intake. For women, the variables age, marital status, domiciliary residence, and self-reported health as good/very good were associated with the adequate intake of fruits and vegetables. Men with 65 years or more showed association with the outcome variable. The consumption of unhealthy foods proved inversely associated with adequate consumption of FV for both genders. Conclusion: The prevalence of adequate FV intake observed in the population of Brazil’s Midwest region in 2012 can be considered low. The associations between the outcome and variables of food intake and physical activity were similar between the genders, however, among women there was an association of recommended fruit and vegetable intake with age, place of residence, marital status and self-reported health status as good/very good. Considering the low FV intake in this population and the differences between the genders, interventions to improve the consumption of these foods could be made in a globalized way.